Koneksi Politik Memperkuat Good Corporate Governance Terhadap Penghindaran Pajak - Suwandi Suwandi (Akuntabilitas, 2021)
The purpose of this study was to examine the influence of the interaction of political connections with Good Corporate Gavernance (GCG) on tax avoidance. The samples in this study were all manufacturing companies on the Indonesia Stock Exchange (BEI). The method of determining the sample using purposive sampling in accordance with predetermined criteria and obtained a sample of 279. The analysis technique is multiple linear regression. The test results of multiple linear regression analysis show that GCG has no effect on tax avoidance, while the interaction of political connections with Good Corporate Gavernance (GCG) has a significant effect on tax avoidance, so Good Corporate Gavernance (GCG) is proxied by the board of commissioners and audit committee purely moderating while the board of directors is a pseudo variable or quasi moderating. Tax avoidance is an effort to ease the tax burden by not violating the law. Tax avoidance is a complex and unique issue because it does not violate the law (legal) but is unwanted by the government because it reduces state revenue.